Weed infestation of narrow-leaved lupine crops in grain-grass-rowed crop rotation in the North-West of Russia - A. M. Shpanev (Аграрная наука Евро-Северо-Востока)
The results of the long term (2012–2018) study of weed infestation of green fallow fields with narrow-leaved lupin in the crop rotation including cereals, grasses and row crops in the North-West region of Russia (Leningrad region) are presented. The assessment of weediness in the narrow-leaved lupine variety Oligarch crops was carried out annually at 24 permanent survey sites (0.1 square meter). Based on the results of the surveys, the formation of a diverse and constant species composition of weeds (from 15 to 25 species), mainly of medium and severe degree of weediness (141–593 specimens per square meter), with the proportion of young plants ranging from 90.4 to 99.7 %. The mass species of weeds were lamb’s quarters, field pansy, corn spurry, hemp-nettles, fumitory, shepherd’s purse, prevalent perennial weeds were field sowthistle, coltsfoot, red sorrel, couch grass, marsh woundwort. The prevailing influence of weather conditions and individual characteristics on the weed infestation of narrow-leaved lupine crop has been determined. The combined effect of two factors was expressed by 47.7, 57.8 and 47.1 % in terms of species abundance, initial abundance and final phytomass of weeds, respectively. Long term application of mineral fertilizers led to an increase in the number of annuals (by 1.5–1.6 times) and a decrease in the density of growth of perennial weed species (by 1.6–1.9 times). The influence of the integrated plant protection system used in the crop rotation was manifested in a significant decrease in the density of perennial weed species (by 4.6 times) in narrow-leaved lupine crop.